In silico Assessment of the Genotypic Distribution of Virulence and Antibiotic Resistance Genes in Vibrio cholerae (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Vibrio cholerae has long been reported as an important cause of death in developing countries. The study detected the virulence and antibiotic resistance gene of eight V. cholerae isolates through in silico tools. Cholera toxins, ctxA and ctxB were found in six isolates (75%). Seventy-five percent isolates were also found to be positive for zonula occludens toxin, zot which is known to increase the permeability by altering the tight junction of the small intestine. Accessory cholera enterotoxin ace, responsible for fluid accumulation, was detected in four V. cholerae strains. Seven isolates (87.5%) were positive for toxin-coregulated pilus, tcp which helps the bacteria to adhere to gut mucosa. Both ompW and toxR genes were found in 87.5% of the isolates. Twenty-five percent isolates harboured strA, strB, sulII, dfrA1, floR genes and SXT element demonstrating that they were multidrug-resistant (MDG) bacterium. One isolate was found to be positive for tetA gene while no erythromycin resistance gene, ermA and ermB was found. Virulence genes were found in all genotypes indicating that their distribution was not genotypeoriented while genotype 2 harboured no antibiotic resistance genes. This data helps to predict virulence genes associated with cholera and also demonstrates the presence of antibiotic resistance genes. Bacteria acquired the antibiotic resistance gene through natural process which cannot be stopped. So by analyzing the resistance pattern we can choose appropriate antibiotics. In silico study helps us to predict the antibiotic resistant genotypes and can easily identify antibiotic resistant strains which help us to treat cholera infections and reduce the morbidity and mortality rate of the infected individuals.Dhaka Univ. J. Pharm. Sci. 16(1): 77-85, 2017 (June)